Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX